Projecting the future redistribution of Pinus koraiensis (Pinaceae: Pinoideae: Pinus) in China using machine learning - Chen, Xin; Xiao, Kaitong; Deng, Ruixiong; Wu, Lin; Cui, Lingjun; Ning, Hang; Ai, Xunru; Chen, Hui (Frontiers in Forests and Global Change, 2024)
As an important coniferous tree in northeast China, Pinus koraiensis not only maintains the stability of the forest ecosystem at high latitudes but also plays a crucial role in regional socioeconomic development. With the intensification of climate change in recent years, the stability of P. koraiensis habitats is constantly disturbed by external uncertain environmental factors, which greatly affects the geographical distribution of P. koraiensis. However, its geographical distribution is still unclear, which greatly hinders further understanding of the ecological process of P. koraiensis. Consequently, it is particularly important to explore the potential distribution and migration of P. koraiensis during several critical periods. Random forest (RF) was used to establish the redistribution of P. koraiensis.The results showed that temperature seasonality and precipitation coldest quarter were the key factors limiting the current distribution of P. koraiensis. Currently, P. koraiensis is mainly distributed in the Lesser Khingan Mountains and Changbai Mountains, with a total suitable area of approximately 4.59×10 5 km 2 . In the past, the historical distribution of P. koraiensis during the LIG period was basically consistent with the current distribution range, but its distribution range was more complete.In the LGM period, the suitable distribution of P. koraiensis became fragmented, especially at the connection between the Lesser Khingan Mountains and the Changbai Mountains. Under future climate scenarios, the suitable distribution of P. koraiensis is projected to increase, while the highly suitable distribution will be reduced. The dramatically worrying change is that the suitable habitats of P. koraiensis are gradually breaking and separating in the junction zone between the Lesser Khingan Mountains and Changbai Mountains, which will cause the ecological corridor to break. The shifts in the distribution centroid indicated that the P. koraiensis population will migrate northward. However, it remains to be verified whether long-distance migration can be achieved without human assistance.Our results can provide some solutions for protection and management strategies for P. koraiensis populations and the impact of climate change, shedding light on the effectiveness of management responses.